Using the Self-Controlled Tree-Temporal Scan Statistic to Assess the Safety of Live Attenuated Herpes Zoster Vaccine. Issue 7 (7th May 2019) - Yih, W Katherine; Kulldorff, Martin; Dashevsky, Inna; Maro, Judith C
Abstract: The self-controlled tree-temporal scan statistic allows detection of potential vaccine- or drug-associated adverse events without prespecifying the specific events or postexposure risk intervals of concern. It thus opens a promising new avenue for safety studies. The method has been successfully used to evaluate the safety of 2 vaccines for adolescents and young adults, but its suitability to study vaccines for older adults had not been established. The present study applied the method to assess the safety of live attenuated herpes zoster vaccination during 2011–2017 in US adults aged ≥60 years, using claims data from Truven Health MarketScan Research Databases. Counts of International Classification of Diseases diagnosis codes recorded in emergency department or hospital settings were scanned for any statistically unusual clustering within a hierarchical tree structure of diagnoses and within 42 days after vaccination. Among 1.24 million vaccinations, 4 clusters were found: cellulitis on days 1–3, nonspecific erythematous condition on days 2–4, "other complications . . ." on days 1–3, and nonspecific allergy on days 1–6. These results are consistent with local injection-site reactions and other known, generally mild, vaccine-associated adverse events and a favorable safety profile. This method might be useful for assessing the safety of other vaccines for older adults.